The influence of certain cognitive abilities on situation efficiency of basketball players - Jakovljevic, S.; Pajic, Z.; Gardasevic, B. (Facta Universitatis: Series Physical Education and Sport, 2015)
The aim of this study was to examine the influence of certain cognitive abilities on the efficiency of shooting and overall efficiency of professional basketball players. The research was conducted on 48 professional basketball players who played in the last season of Serbia and Montenegro league. Minimal conditions the players had to fulfill in order to be included in the research were the following: that they participated in at least 12 games (of 22), spent at least five minutes on court per game, and that they had at least two field shots and two free throws per game. Independent variables were acquired by using five tests of cognitive abilities (Domino test D-48, P1, S1, F1 and F2), and dependent variables were the data on situation efficiency of basketball players when shooting (efficiency of field shots, free throw efficiency, average points per game and index of efficiency). Poor/moderate correlation between three independent variables: general intelligence, perceptive identification and perceptive analysis and logical conclusions and dependent variable index of efficiency were shown. The regression analysis - Stepwise method obtained a significant influence of only one independent variable - perceptive analysis and logical conclusions on only one dependent variable index of efficiency.